Análisis al comercio ambulante del barrio central del cantón La Maná y su incidencia en la rentabilidad de las Pymes. - Chanalata Iza, Jaime Jeancarlo (2022)
The analysis of itinerant trade in the central neighborhood of La Maná canton was developed both in the itinerant trade, which is made up of 228 people, and in the SMEs of the canton, that is, the owners have a population of 3,800 people. The general objective of the research is to analyze the street trade of the La Maná canton and its impact on the profitability of SMEs. It is said that informal commerce has been present for a long time, it is a way of subsisting for those people who have not been able to get a stable and permanent job, for which they resort to street vendors or also known as informal commerce, the people who do it themselves. they make use of empirical knowledge and apply intuitive marketing which they say is the one that makes people go to places of great social concentration at specific times. Profitability is the percentage of return of the money that a company or economic activity has with respect to what has been invested. This helps us to measure if a company is growing, maintaining itself or tending to go bankrupt. SMEs are economic entities that are dedicated to generating work and economic and commercial movement in the places where they are developed. The methodology used was the one that provided the most help for the development of the research, such as field research, the analytical method and the survey as a technique, to mention the most relevant. These allowed us to reach many conclusions and the most notable is the one that mentions that the relationship of itinerant commerce with the profitability of SMEs is sectorized and that it is perceived in a counterproductive way for SMEs due to the amount of items they pay given that the SME sector has more taxes than street vendors. This project also helped determine costs, sales, equity, profit margin, liquidity ratio, indebtedness and return on equity, in addition to these many more important issues were addressed.